Workplace Learning Subjective Motives and Supervisor Support Matter - Baron, Stefan; SpringerLink (Online service) (Wiesbaden : VS Verlag für Sozialwissenschaften, 2011)
Stefan Baron gathers information on reasons for the consistently low further training rates of both older and less educated employees, and provides suggestions to increase their participation in further training. He shows that employees are not solely rational decision-makers and that training decisions are affected by different educational motivation and investment risks. In particular, lacking confidence in own training competence can be a handicap for future training participation. Still, supervisors can help to strengthen confidence levels, but in many cases they are not trained to provide emotional support and may run the risk of following stereotypes and prejudices about older and less educated employees. As a consequence, both groups might not get the support they need for taking part in further training.
Keywords: Social sciences; Sociology; Economic sociology; Social Sciences; Social Sciences, general; Organizational Studies, Economic Sociology; Sociology, general; Electronic books